Design and experimental validation of a new condenser of an automotive air conditioning unit to address non-uniform air velocity distributions. (November 2021) - Li, Wanyong; Tu, Jian; Liu, Yusheng; Wang, Dandong; Shi, Junye; Chen, Jiangping
Highlights: The front anti-collision beam in a car leads to air maldistribution. A six-path condenser is an optimization of the traditional four-path condenser. The new condenser shows better capacity with the anti-collision beam. The cooling performance of automobile air conditioning system is improved. Abstract: To improve the efficiency of automobile air conditioning and reduce the impact of non-uniform air velocity distributions caused by the front anti-collision beam on automobiles, we designed a new six-process condenser and tested it under different working conditions. A baffle was positioned to simulate the anti-collision beam during the experiment. We analyzed the condenser by itself and the system level performance of this newly designed condenser under three working conditions compared to a traditional four-process condenser. Condenser heat exchange capacity, condenser inlet pressure, system refrigerant flow rate, refrigerant flow resistance, thermal imaging of condenser outlet air, overall system cooling capacity, and coefficient of performance were compared. The coefficient of performance of the system with this new condenser improved by 8.5%, 7.8%, and 10.3% for the three tested working conditions.